Solving linear equations and inequalities: Systems of linear equations in two unknowns
Solving by the substitution method
Solve the following system of equations with unknowns \(x\) and \(y\) by using one equation to express \(x\) in \(y\). Subsequently substitute this expression for \(x\) in the other equation so that you get a linear equation with unknown \(y\). \[ \lineqs{ 6 x+5 y &=& 3 \cr -x-y &=& -2 \cr}\]
Enter the answer in the form \(x=a\land y=b\) with proper values of \(a\) and \(b\). You can enter the system below as a starting point for the reduction to a solution.
\[ 6 x+5 y=3 \land -x-y=-2 \]
Enter the answer in the form \(x=a\land y=b\) with proper values of \(a\) and \(b\). You can enter the system below as a starting point for the reduction to a solution.
\[ 6 x+5 y=3 \land -x-y=-2 \]
Unlock full access